The Effect of Transformational Leadership and Career Development on Employee Performance - Tarigan, Rut; Hendaryan, Dudi (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Employee performance is a key factor in achieving organizational goals because it directly impacts a company's productivity and competitiveness in the era of global competition. Many organizations face challenges in sustainably improving employee performance given the changing work environment, increasing competency demands, and the need to maintain motivation and commitment. This study aims to analyze the influence of transformational leadership and career development on employee performance at PT. Nalsal Indo Perkasa. The background indicates problems related to a leadership style that is considered rigid and a lack of appreciation for employees, accompanied by suboptimal career development. The research method used is descriptive and verification with a quantitative approach. Data were collected through questionnaires to 40 employees and analyzed using validity and reliability tests, as well as path analysis. The results of the study show a significant influence of transformational leadership and career development, both partially and simultaneously, on employee performance. Simultaneously, both variables influence performance by 69.84%. The findings emphasize the importance of inspirational leadership and a clear career development system to support productivity.